2019
DOI: 10.1136/annrheumdis-2018-214970
|View full text |Cite
|
Sign up to set email alerts
|

Gradual tapering TNF inhibitors versus conventional synthetic DMARDs after achieving controlled disease in patients with rheumatoid arthritis: first-year results of the randomised controlled TARA study

Abstract: ObjectivesThe aim of this study is to evaluate the effectiveness of two tapering strategies after achieving controlled disease in patients with rheumatoid arthritis (RA), during 1 year of follow-up.MethodsIn this multicentre single-blinded (research nurses) randomised controlled trial, patients with RA were included who achieved controlled disease, defined as a Disease Activity Score (DAS) ≤ 2.4 and a Swollen Joint Count (SJC) ≤ 1, treated with both a conventional synthetic disease-modifying antirheumatic drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 30 publications
(41 reference statements)
1
29
0
1
Order By: Relevance
“…The recent STRASS study of RA-patients in remission (DAS28 < 2.6) found that relapse was observed more frequently in patients placed on a progressively increased spacing of TNF-blockers injections than those maintained on their previous dosing regimen (76.6% vs 46.5%, p = 0.0004), however the equivalence of the two strategies could not be demonstrated due to an underpowered trial [23]. Most recently, the TARA (TApering strategies in Rheumatoid Arthritis) study, the first randomized controlled study comparing a de-escalation strategy with reduction and discontinuation of synthetic DMARDs versus TNF-blockers, highlighted the importance of first reducing treatment with bDMARDs prior to initiation of synthetic DMARDs therapy [24]. Concerning TCZ tapering, several strategies have been tried, including discontinuation TCZ infusions [12,13], and gradually increasing the RTI to a fixed interval (eg.…”
Section: Discussionmentioning
confidence: 99%
“…The recent STRASS study of RA-patients in remission (DAS28 < 2.6) found that relapse was observed more frequently in patients placed on a progressively increased spacing of TNF-blockers injections than those maintained on their previous dosing regimen (76.6% vs 46.5%, p = 0.0004), however the equivalence of the two strategies could not be demonstrated due to an underpowered trial [23]. Most recently, the TARA (TApering strategies in Rheumatoid Arthritis) study, the first randomized controlled study comparing a de-escalation strategy with reduction and discontinuation of synthetic DMARDs versus TNF-blockers, highlighted the importance of first reducing treatment with bDMARDs prior to initiation of synthetic DMARDs therapy [24]. Concerning TCZ tapering, several strategies have been tried, including discontinuation TCZ infusions [12,13], and gradually increasing the RTI to a fixed interval (eg.…”
Section: Discussionmentioning
confidence: 99%
“…Доводом в пользу подобной практики может служить и тот факт, что ГИБП или таргетные БПВП чаще всего назначают пациентам, у которых стандартные БПВП оказываются недостаточно эффективными. В рандомизированном исследовании TARA были сопоставлены результаты постепенной отмены (в течение 6 мес) стандартных БПВП или ингибиторов ФНОα у 189 больных РА, у которых была достигнута ремиссия заболевания на фоне комбинированной терапии двумя препаратами [29]. Полной отмене БПВП предшествовало последовательное двукратное снижение дозы в два раза под контролем активности РА, в то время как ингибитор ФНО-α отменяли после увеличения интервала между введениями в два раза и последующего снижения дозы.…”
Section: исследование Oral-shiftunclassified
“…IL-17 and TNF-α levels were reported to have correlation with RA activity and thus were currently selected as therapy targets (13,14). We analyzed the presence of possible correlation between AMPK levels with IL-17 and TNF-α in the serum samples.…”
Section: Serum P-ampk-α1 Levels Positively Correlated With Disease Acmentioning
confidence: 99%